1994
DOI: 10.1143/jjap.33.1876
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance and Mössbauer Studies of CaS:Eu Synthesized Using the Flux Method

Abstract: CaS:Eu phosphors were synthesized using the flux method. ESR and Mössbauer spectroscopies show the coexistence of Eu3+ and Eu2+. Eu3+ and Eu2+ are mainly observed in phosphors obtained with Na2S z ((Na) phosphors) and K2S z fluxes ((K) phosphors), respectively. The Eu2+ fraction in (K) phosphors varies with total Eu content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
4
9
0
Order By: Relevance
“…In bulk materials, europium ions substitute calcium ions in the cubic symmetry lattice. 18,22 Therefore it follows that the europium ions reside as internal ions substituting calcium ions in the CaS lattice.…”
Section: Dopant Europium Atoms In Calcium Sulfide Nanoparticlesmentioning
confidence: 99%
“…In bulk materials, europium ions substitute calcium ions in the cubic symmetry lattice. 18,22 Therefore it follows that the europium ions reside as internal ions substituting calcium ions in the CaS lattice.…”
Section: Dopant Europium Atoms In Calcium Sulfide Nanoparticlesmentioning
confidence: 99%
“…They suggested that Eu> had two kinds of sites in CaS, forming center A (isolated Eu> center) and center B (paired Eu>-Eu>) (11). M. Pham-Thi et al observed two oxidation states of Eu> and Eu> in CaS prepared in alkaline polysulfide flux, however, they observed Eu> luminescence in CaS only at low temperature as many other investigators (6,12).…”
Section: Introductionmentioning
confidence: 93%
“…Europium has two isotopes of Eu and Eu with nuclear spin 5/2 (the natural abundance and nuclear g factor of Eu and Eu are: 47.8%, 1.39 and 52.2%, 0.61, respectively) (10,12), therefore, Eu> in cubic symmetry is expected to show two sets of six hyperfine lines with equal intensity. Fig.…”
Section: Epr Properties Of Cas : Eu Lamentioning
confidence: 99%
“…For CaS:Eu luminophors, Danilkin et al [136] observed only one Mössbauer absorption peak, corresponding to Eu3+ ions. Pham-Thi et al [103] synthesized CaS:Eu using the flux method with Na and K. The Mössbauer spectrum of the sample prepared with Na polysulphide flux showed only Eu3+ absorption while with K flux both ions were detected.…”
Section: Materials Overviewmentioning
confidence: 99%